Women’s Participation in Smart Manufacturing and Industry 4.0 - Kumar, Vishwajeet (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Fourth Industrial Revolution (Industry 4.0) is reshaping global manufacturing through the integration of advanced technologies such as AI, IoT, robotics, and cyber-physical systems. While these advancements offer significant economic potential, women remain underrepresented in Smart Manufacturing, particularly in India. This study investigates women’s participation in Industry 4.0, analyzing labor force data, STEM education trends, skill development initiatives, and policy frameworks. Findings reveal that although female STEM enrollment has increased to 37.8% in 2023, only 16.5% of women are employed in manufacturing, and even fewer hold advanced technical roles. Structural barriers including gender bias, skill gaps, and cultural norms continue to hinder women's full inclusion. The study concludes that targeted policy reforms, advanced skill training, and workplace flexibility are essential to close this gender gap, which could boost India’s GDP by 3-4%.